Magnetoelectric CoFe2O4/polyvinylidene fluoride electrospun nanofibres. Issue 17 (14th April 2015) - Gonçalves, R.; Martins, P.; Moya, X.; Ghidini, M.; Sencadas, V.; Botelho, G.; Mathur, N. D.; Lanceros-Mendez, S.
Abstract : Magnetic field induces changes in the piezoelectric response of the nanofibres. Abstract : Magnetoelectric 0–1 composites comprising CoFe2 O4 (CFO) nanoparticles in a polyvinylidene fluoride (PVDF) polymer-fibre matrix have been prepared by electrospinning. The average diameter of the electrospun composite fibres is ∼325 nm, independent of the nanoparticle content, and the amount of the crystalline polar β phase is strongly enhanced when compared to pure PVDF polymer fibres. The piezoelectric response of these electroactive nanofibres is modified by an applied magnetic field, thus evidencing the magnetoelectric character of the CFO/PVDF 0–1 composites.